Implementasi Perda Tentang Retribusi Jasa Umum Terhadap Pengelolaan Retribusi Pasar Di Wonomulyo Kab Polewali Mandar - Mustapa, Maslina; Hamid, Hariyanti; Sundari (CV. Multi Kreasi Media, 2024)
Implementation of the Regional Regulation Concerning Public Services Levy on Market Levy Management in Wonomulyo, Polewali Mandar Regency, guided by Hariyanti Hamid and Sundari. The purpose of this study is to understand the implementation of the Law No. 21 of 2010 on the State's Distribution of Wages to the Wonomulyo Regional Government, Polewali Mandar district. The sample of the research consists of 841 people and 89 sellers. The sampling technique used is Purposive Sampling. This type of study is descriptive quantitative. The data collection techniques used are observations, interviews, research in libraries, and questionnaires. Data analysis techniques employed include statistical analysis, statistical evaluation of data quality (validity and reliability tests), and linear regression analysis with simplicity. The results of the research show that the implementation of regional regulation No. 21 2010 has an average score of 74% good. Market levy management with an average value of 79% is good. Factors that influence management consist of changes that are always good with a percentage of 64%, mistakes with a percentage of 69%, the need for managers to delegate authority with a percentage of 58%.